Pengaruh Teknik Distraksi Menonton Kartun Animasi Terhadap Skala Nyeri Pada Anak Usia Pre School Saat Pemasangan Infus Di Rumah Sakit: The Effect of Animated Cartoon Distraction Technique on Pain Scale in Preschool-Aged Children During Intravenous Cannulation in Hospital - Utami, Tuti Asrianti; Purwanti, Purwanti; Prabawati, Dewi (Chakra Brahmanda Lentera Institute, 2026)
Children of all ages can experience illness. One of the many invasive procedures that hospitalized children will undergo is IV insertion. IV insertion is painful because it can cause pain, so management is needed to minimize pain. One of the non-pharmacological pain management is to use distraction techniques that can reduce the pain scale during infusion. This study aims to analyze the effect of distraction techniques watching animated cartoons on the pain scale during infusion of children pre school at X Jakarta Hospital. The research design used was Quasi Experiment Non Equivalent Control Group Design involving 70 respondents who were divided into an intervention group of 35 respondents and a control group of 35 respondents. The research instrument used a pain measurement sheet wong baker faces scale. The results of the Man Whitney test analysis showed that there was an effect of distraction techniques watching animated cartoons on the pain scale in children pre school during infusion at X Jakarta Hospital (p value = 0.000 <0.05). It is expected that nurses can start applying infusion installation with distraction techniques, especially audiovisual distraction techniques to minimize pain in pediatric patients.